1999
DOI: 10.1126/science.286.5438.272
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Nonlinear Elasticity of the Crust from the Mw7.6 Manyi (Tibet) Earthquake

Abstract: Satellite synthetic aperture radar (SAR) interferometry shows that the magnitude 7.6 Manyi earthquake of 8 November 1997 produced a 170-kilometer-long surface break with up to 7 meters of left-lateral slip, reactivating a N76 degrees E quaternary fault in western Tibet. The radar interferometric map reveals asymmetric, along-strike displacement profiles between the two sides of the surface rupture, a pattern that cannot be explained with linear elastic theory. This observation suggests that the elastic moduli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
189
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(202 citation statements)
references
References 41 publications
8
189
1
1
Order By: Relevance
“…Using the regional mainshock location as the calibration event, the relocations lie on the 180 km trace of the surface rupture that was defined using InSAR [Peltzer et al, 1999] The body wave inversion indicates that most of the moment release occurred early in the rupture near the hypocenter over a relatively small region of the fault. Most of the moment was released above 15 km, and there is little indication of alongstrike directivity in the body waves.…”
Section: Summary Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the regional mainshock location as the calibration event, the relocations lie on the 180 km trace of the surface rupture that was defined using InSAR [Peltzer et al, 1999] The body wave inversion indicates that most of the moment release occurred early in the rupture near the hypocenter over a relatively small region of the fault. Most of the moment was released above 15 km, and there is little indication of alongstrike directivity in the body waves.…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…The largest slip was focused near the epicenter, but the overall rupture probably included additional slip to the west-southwest of the epicenter. The primary slip seems to have been concentrated in a region little more than 50 km wide, but if we include the secondary slip, the total rupture length is of the order of 120-140 km, which is smaller the defined surface rupture [Peltzer et al, 1999]. This increases the likelihood that the subevent is not an early aftershock.…”
Section: 33mentioning
confidence: 99%
See 1 more Smart Citation
“…The seismicity maps of Ma [1989] and SSBC [1992] showed that numerous M--5-6 earthquakes occurred in the Qaidam basin from mid-1960s to early 1990s, mostly within the Qimen Tagh thrust system and in the region south of Qinghai Lake. The largest earthquake in the region was an M: 7.6 left slip event (the Manyi earthquake) in 1997 along a nearly east-west trending fault at the eastern termination region of the Kunlun fault [Peltzer et al, 1999] (Figure 2). …”
Section: Introductionmentioning
confidence: 99%
“…earthquake produced a 170-km-long surface-rupture zone along the westernmost strand of 137 the KF (~86°E to 88°E) with a maximum slip of 7 m (Peltzer et al, 1999; Van The earthquake sequence of these five events provides an excellent chance to decipher 147 how ΔCFS on the KF evolved over the past several decades and how earthquakes 148 communicated with each other by stress transfer. On the other hand, it also provides a good 149 opportunity to outline the segments which have experienced large build-up of stress.…”
Section: Introduction 38mentioning
confidence: 99%